Criminal Liability against Children as Perpetrators of Theft - Iswantoro Iswantoro; Maryanto Maryanto (Universitas Islam Sultan Agung, 2020)
The objectives of this study are: 1. To analyze criminal responsibility towards children as perpetrators of criminal acts of theft in the jurisdiction of the Pati District Court. 2. To analyze constraints in the implementation of criminal responsibility against children as perpetrators of criminal acts of theft in the jurisdiction of the Pati District Court and their solutions. The research method used is juridical empirical. Research results and discussion The background of the crime of theft committed by children is various factors, including; lack of parental attention and supervision. The occurrence of the criminal act of theft, not only raises legal problems but also creates economic problems and social problems in the community, because it is an act that is detrimental to the state and to this act the state reacts with punishment as the last resort (Ultimum Remedium)Accountability for the verdict of case Number: 5 / Pid.Sus-Anak / 2017 / PN Pati, with the defendant WES Known as Wn Bin S having been legally and convincingly proven guilty of committing the crime of